Biblical Intertextuality in Ferran de Pol - Josep V. Garcia Raffi; Xavier Garcia Raffi (Interlitteraria)
The main objective of this article is to offer an intertextual study of the presence of the Bible in the work of Ferran de Pol. Intertextuality is understood as the relationship that exists between two or more texts when we can identify in one of them more or less explicit phrases taken from others, in this case from the Bible. We do not analyse any religious intention of the author, but we note that the Bible was undoubtedly one of his formative books. We find the greatest biblical presence in his novels Érem quatre (‘We Were Four’, 1960), Miralls tèrbols (‘Cloudy Mirrors’, 1966) and the unpublished Ella, jo i el càntic (She, I and the Song, 1987). Ferran de Pol’s rewriting of the Bible has multiple and heterogeneous functions: in some cases it acts as the central axis of a specific work, in others it has compositional, rhetorical, satirical, conceptual or parodic functions.